ENHANCING PRESCHOOL INSTITUTION PERFORMANCE THROUGH STRATEGIC PERSONNEL MANAGEMENT: INSIGHT FROM RA RAHMAH EL YUNUSIYYAH - Wahyuni, Sri Intan; Sabila, Tasya; Ramadani, Laili; Qadafi, Muammar (Al Fitrah: Journal Of Early Childhood Islamic Education, 2024)
The management of educators and education personnel is one indicator of the quality of a school. To guarantee the quality of schools, there is a need for the management of educators and education personnel. This research aims to describe the management of educators and education personnel at RA (Raudlatul Athfal) el Yunisiyyah, a part of a formal early childhood education institution (PAUD). This research uses a descriptive qualitative method by collecting data through documentation, interviews, and observation.  The results of the research show that the functions of education management and educational staff carried out at the aspects of planning, organizing, implementing, supervising, and terminating are carried out at RA Rahmah el Yunusiyyah, Padang Panjang. In its implementation, RA Rahmah el Yunusiyyah is assisted by the HR division of Diniyyah Puteri College and the Department of Education.